Conspecific alarm calls prevent the attenuation of neophobia behavior in wild-caught house sparrows (Passer domesticus) - Kimball, Melanie G.; Masri, Danna F.; Gautreaux, Eve B.; Stansberry, Keegan R.; Kelly, Tosha R.; Lattin, Christine R. (Frontiers in Bird Science, 2024)
Some individuals respond to new objects, foods, or environments with wariness (neophobia), whereas others are willing to approach and explore. Because novel stimuli can represent both dangers and resources, group-living species may show adaptive plasticity in neophobia in response to social cues. To better understand how conspecific calls can influence neophobia in a highly gregarious species, we exposed individual house sparrows (Passer domesticus) to either conspecific alarm calls (n = 12), conspecific contact calls (n = 12), or no playback (n = 12) and measured latency to feed in the presence of novel objects. We also measured novelty responses with no sound the week before and after the sound treatment week for all individuals. Relative to no playback and contact calls, we predicted that conspecific alarm calls would increase neophobia behavior during the acoustic trial and that these effects would persist the week after exposure. Instead, we found that individuals in the contact call and no playback groups became less neophobic as weeks progressed, while the alarm call group showed no attenuation of neophobia. There was a significant interaction between week and treatment, where neophobia responses over the three weeks were significantly different for individuals exposed to alarm calls compared to the contact and no playback groups combined. These results suggest that house sparrows learn social information about potentially threatening stimuli from conspecific alarm calls; here, that novel objects may be dangerous.